Respuesta :

Answer:

[tex]\boxed { \frac{7}{5}y } \to \: \boxed {y+ \frac{2}{5}y }[/tex]

[tex]\boxed { \frac{3}{5}y } \to \: \boxed {y - \frac{2}{5}y }[/tex]

Step-by-step explanation:

We need to simplify

[tex]y + \frac{2}{5}y[/tex]

We collect LCM to get;

[tex] \frac{5y + 2y}{5} = \frac{7y}{5} [/tex]

Therefore:

[tex] \boxed { \frac{7}{5}y } \to \: \boxed {y+ \frac{2}{5}y }[/tex]

Also we need to simplify:

[tex]y - \frac{2}{5}y[/tex]

We collect LCM to get;

[tex]y - \frac{2}{5}y = \frac{5y - 2y}{5} = \frac{3}{5} y[/tex]

Therefore

[tex]\boxed { \frac{3}{5}y } \to \: \boxed {y - \frac{2}{5}y }[/tex]

ACCESS MORE